KRIT1 Protein Depletion Modifies Endothelial Cell Behavior via Increased Vascular Endothelial Growth Factor (VEGF) Signaling - DiStefano, Peter V. (J Biol Chem, 2014)
Disruption of endothelial cell-cell contact is a key event in many cardiovascular diseases and a characteristic of pathologically activated vascular endothelium. The CCM (cerebral cavernous malformation) family of proteins (KRIT1 (Krev-interaction trapped 1), PDCD10, and CCM2) are critical regulators of endothelial cell-cell contact and vascular homeostasis. Here we show novel regulation of vascular endothelial growth factor (VEGF) signaling in KRIT1-depleted endothelial cells. Loss of KRIT1 and PDCD10, but not CCM2, increases nuclear β-catenin signaling and up-regulates VEGF-A protein expression. In KRIT1-depleted cells, increased VEGF-A levels led to increased VEGF receptor 2 (VEGFR2) activation and subsequent alteration of cytoskeletal organization, migration, and barrier function and to in vivo endothelial permeability in KRIT1-deficient animals. VEGFR2 activation also increases β-catenin phosphorylation but is only partially responsible for KRIT1 depletion-dependent disruption of cell-cell contacts. Thus, VEGF signaling contributes to modifying endothelial function in KRIT1-deficient cells and microvessel permeability in Krit1(+/−) mice; however, VEGF signaling is likely not the only contributor to disrupted endothelial cell-cell contacts in the absence of KRIT1.